A Silicon-Based Nanothin Film Solid Oxide Fuel Cell Array with Edge Reinforced Support for Enhanced Thermal Mechanical Stability - Baek, Jong Dae (2017)
A silicon-based micro-solid oxide fuel cell (μ-SOFC) with electrolyte membrane array embedded in a thin silicon supporting membrane, featuring a unique edge reinforcement structure, was demonstrated by utilizing simple silicon micromachining processes. The square silicon supporting membrane, fabricated by combining deep reactive ion etching and through-wafer wet etching processes, has thicker edges and corners than the center portion of the membrane, which effectively improved the mechanical stability of the entire fuel cell array during cell fabrication and cell operation. The 20 μm thick single crystalline silicon membrane supports a large number of 80 nm thick free-standing yttria-stabilized zirconia (YSZ) electrolytes. The fuel cell array was stably maintained at the open circuit voltage (OCV) of 1.04 V for more than 30 h of operation at 350 °C. A high peak power density of 317 mW/cm2 was obtained at 400 °C. During a rigorous in situ thermal cycling between 150 and 400 °C at a fast cooling and heating rate of 25 °C/min, the OCV of the μ-SOFC recovered to its high value of 1.07 V without any drop caused by membrane failure, which justifies the superior thermal stability of this novel cell architecture.